2D black phosphorous nanosheets as a hole transporting material in perovskite solar cells - Muduli, Subas Kumar (2020)
We demonstrate for the first-time liquid exfoliated few layers of 2D Black phosphorus (BP) nanosheets as a hole transporting material (HTM) for perovskite based solar cells. The photoelectron spectroscopy in air (PESA) measurements confirm the low laying valence band level of BP nanosheets (−5.2 eV) favourable for hole injection from CH3NH3PbI3 (MAPbI3). Our results show that ∼25% improvement in power conversion efficiency (PCE) of η = 16.4% for BP nanosheets + Spiro-OMeTAD as an HTM as compared to spiro-OMeTAD (η = 13.1%). When BP nanosheets are exclusively utilised as an HTM, a PCE of η = 7.88% is noted, an improvement over the 4% PCE values observed for HTM free devices. Photoluminescence (PL) quenching of MAPbI3 and impedance measurements further confirm the charge extraction ability of BP nanosheets. The structural and optical characterization of liquid exfoliated BP nanosheets is discussed in detail with the aid of transmission electron microscopy, Raman spectroscopy, absorption spectroscopy and photo-electron spectroscopy.